STRATEGI PENGEMBANGAN AGRIBISNIS KAKAO (STUDI KASUS DI DESA WOLOKISA KECAMATAN MAUPONGGO KABUPATEN NAGEKEO) - Maria Yulita Bei; Ignatius Sinu; I Nyoman Sirma (Buletin Ilmiah Impas, 2020)
This research was conducted in Wolokisa Village, district of Mauponggo, Nagekeo Regency. This research aimed toidentify the strategies applied by farmers in developing cocoa farming,strengthand weakness, opportunities and threats factors indeveloping cocoa farming in Mauponggo district, Nagekeo Regency. Data collection interviews using questionnaires. Analysis of the data used is the SWOT analysis. The results showed that the internal factors influencing the development of the cocoa agribusiness in Wolokisa Village were (1) Availability of land and agro-climate, (2) Number of farmers, (3) Experience of farmers, (4) ) Cocoa quality, (5) Supporting institutions. (6) Farmers' weak management, (7) Simple technology that is still used (8) Poor acceleration (8) Pests and diseases. Although external factors that influence the development of the cocoa agribusiness in Wolokisa Village were: (1) high demand, (2) high prices, (3) clear market goals, (6) fluctuating prices, (7) climate, (8) cocoa producers from other villages. The appropriate strategies for developing cocoa agribusiness in Wolokisa Village are increasing production and better quality to meet demand and obtain high prices and using the experience of farmers and support institutions to reduce competitors.